THE ATLANTIC SLAVE TRADE AND COLONIALISM: REASONS FOR AFRICA’S UNDERDEVELOPMENT? - Ojo, Emmanuel Oladipo (European Scientific Journal, ESJ, 2015)
It is probably an understatement to assert that Africa, the world’s second largest continent, is underdeveloped compared with other continents. Two major exogenous factors often cited for Africa’s development crisis are the so called ‘dual historical injustices’ – the Atlantic slave trade and colonialism. It is often pointed out that while the former almost completely arrested and retarded Africa’s demographical growth for more than three centuries, evoked a perennial state of acrimony and warfare and created a tense and unprecedented atmosphere of insecurity which hindered economic activities and stifled local entrepreneurship and technological drive and dislocated Africa’s socio-economic and political structures and institutions; the latter tied African countries to the apron strings of western imperial powers thereby rendering the pre-conditions necessary for socio-economic and political transformation unachievable. This paper contends that while the history of Africa’s underdevelopment may be traceable to the Atlantic slave trade and colonialism, African leaders had made enormous contributions to the continent’s underdevelopment and backwardness. The paper concludes that irresponsible and irresponsive leadership, vampirism and prodigality, corruption, lack of respect for democratic ideals, insecurity, endemic civil wars, nepotism, etc are the fundamental causes of Africa’s underdevelopment.